TSUKAMOTO FUZZY IN OPTIMIZING THE CREDITWORTHINESS ASSESSMENT PROCESS AT SAVINGS AND LOAN COOPERATIVES - Setiawan, Tabah Heri; Prihatini, Laras (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Savings and Loan Cooperatives are ones of the non-bank institutions whose business activity is the provision of loan. In its business activities, problems often arise, namely non-performing loans which causes no turnover of funds which leads to losses. One of the causes of non-performing loans is the lack of objective creditworthiness assessment. The purpose of this study is to optimize the process of assessing the feasibility of loan applications at Savings and loan credit with assessment criteria: loan value, total income, loan term and collateral value. The tsukamoto fuzzy method was used in this study. Tsukamoto fuzzy method consists of four steps.: fuzzification, Forming fuzzy rules, application of implication functions using the MIN function and defuzzification using the weighted average calculation method. In this research, it was found that Tsukamoto's fuzzy method can be applied to the creditworthiness assessment process at the Saving and Credit Cooperatives. This is because the accuracy rate of the decision results from the tsukamoto method is 93.75%. A total of 60 data out of 64 data are in accordance with the eligibility decision at one of Saving and loan Cooperatives in West Java, Indonesia. Tsukamoto fuzzy method can optimize the credit assessment process in Savings and loan Cooperatives because the eligibility assessment process becomes more efficient and objective.